2017
DOI: 10.14202/vetworld.2017.342-347
|View full text |Cite
|
Sign up to set email alerts
|

Association between udder morphology and in vitro activity of milk leukocytes in high yielding crossbred cows

Abstract: Aim:The present investigation was conducted to study the association between udder morphology and in vitro activity of milk leukocytes in high yielding crossbred cows.Materials and Methods:A total of 48 healthy high yielding crossbred cows were selected for the study. The udder configuration and teat/udder morphology were recorded before milking. Milk samples (100 ml/cow) were collected aseptically. Milk somatic cell counts (SCC) and milk differential leukocyte counts were performed microscopically. Milk leuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…However, a negative correlation between SCC and teat-end to floor distance was found in this study ( P < 0·05). Similar findings were also reported by Sharma et al (2017) in dairy cows.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, a negative correlation between SCC and teat-end to floor distance was found in this study ( P < 0·05). Similar findings were also reported by Sharma et al (2017) in dairy cows.…”
Section: Resultssupporting
confidence: 92%
“…Hussain et al (2013) found a significant ( P < 0·001) association between teat shape (classified as pointed, cylindrical, round and flat) and occurrence of mastitis in Nili-Ravi buffaloes; teats with round and cylindrical shapes being more susceptible to mastitis than pointed teats. On the contrary, Sharma et al (2017) did not observe any association between milk SCC and different teat shapes in high yielding crossbred cows. With respect to teat-end shapes, it has been reported that as the teat-end shape changes from pointed toward flat and inverted, SCC increases (Seykora & McDaniel, 1985).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…High milk-producing cows are under stress of milk production, and their immunity becomes low leading to more SCC in their milk [ 29 ]. High milk SCC not only negatively affects milk yield but also milk composition and quality [ 30 ], and younger cows due to their low milk-producing ability have lower SCC [ 31 ].…”
Section: Factors Affecting Milk Sccmentioning
confidence: 99%
“…Effects of lactation number and lactation month on various udder morphological traits (including front teat diameter) were observed in Holstein cows (Ceyhan et al, 2015). Furthermore, Sharma et al (2017) noted that udder morphological traits (including teat shape and size) could have an impact on milk leukocyte counts, and, hence, udder health, in crossbred cows. Nevertheless, no relation was reported between teat characteristics and mammary development per se.…”
Section: Discussionmentioning
confidence: 97%